Are online consumers protected from geo-blocking practices within the European Union?. (28th March 2018) - Flórez Rojas, Maria Lorena
Abstract: Geo-blocking as a technological protection measure directly affects e-commerce in the European Union, reinforcing discriminatory practices in the online world. The first attempt to fight discrimination in cross-border trade was Article 20 of the Services Directive, which describes the non-discrimination principle. However, this provision has failed in practice due to its large interpretative uncertainties and lack of enforcement. In this view, discriminatory practices have been a constant in the online market and they have intensified due to the use of new geolocation technologies. This article presents the possibility to use provisions of the Treaty on the Functioning of the European Union (TFEU) to tackle geo-blocking practices. The article also considers the new proposal on addressing geo-blocking and it gives some insights regarding the problems of applicability and scope that can open the possibility for consumers to use Article 18 TFEU as legal bases for cases related to geo-blocking practices.